PENDAMPINGAN KAUM MUDA MELALUI INTEGRASI BETERNAK AYAM DAN LELE SEBAGAI SARANA BERMISI - Tameon, Sance Mariana; Wila, Amelia Mariana; Babu, Rini Septiana; Wiawu, Dorkas Dopi Ata; Tefa, Yusmina (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2025)
The aim of this PkM activity is to provide training to young men and women so that they can create business opportunities for themselves and also raise livestock. Young people are trained to proclaim God's love through what they do. The involvement of young people is an important part in developing their personal potential and also as a means for them to preach God's love and become an example for others in managing God's natural creation.Â  By taking part in this training, young people can meet their financial needs independently without depending on their parents. This PKM activity is carried out using four (4) pathways, namely diagnosis (initial survey using participant observation and interview techniques), planning action, taking action (training and mentoring), and evaluating action. Facilitator assistance is carried out until harvest time so that the youth will continue to be supervised until they produce produce for sale. Apart from that, the youth are also equipped to continue praying and believing that God will give success to all their efforts while applying the techniques taught by the facilitator. The young people are very enthusiastic and happy with this PKM activity and are happy because they have learned new things that have an impact on their future